2016
DOI: 10.1186/s12871-016-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of continuous intravenous infusion and two bolus injections of remifentanil on haemodynamic responses during anaesthesia induction: a prospective randomised single-centre study

Abstract: BackgroundRemifentanil is an effective drug for protecting against adverse haemodynamic responses to tracheal intubation. We compared the haemodynamic responses during anaesthesia induction between continuous intravenous (IV) infusion and two bolus injections of remifentanil.MethodsThis prospective, randomised, open-label, single-centre study included patients with American Society of Anesthesiologists physical status I-II, scheduled to undergo elective surgery under general anaesthesia. Patients were randomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…A significant drop of SBP during T2 stage illustrates a huge influence of remifentanil to hemodynamics, and the influence lasts to stage T3. This is in line with Toyoaki et al and Park et al's researches where BP is significantly decreased from baseline after anesthesia induction with remifentanil . We give a rapid infusion of normal saline to increase the SBP and there are no differences of SBP in the stage T4 and T5.…”
Section: Discussionsupporting
confidence: 90%
“…A significant drop of SBP during T2 stage illustrates a huge influence of remifentanil to hemodynamics, and the influence lasts to stage T3. This is in line with Toyoaki et al and Park et al's researches where BP is significantly decreased from baseline after anesthesia induction with remifentanil . We give a rapid infusion of normal saline to increase the SBP and there are no differences of SBP in the stage T4 and T5.…”
Section: Discussionsupporting
confidence: 90%
“…3,4 Another possible reason for the greater reduction in blood pressure that was observed in our study could be because of the relatively low volume of intravenous fluid loading we used before induction. Maruta et al 13 compared the effect of a continuous infusion with bolus administration of remifentanil and evaluated the reason in treated and untreated subgroups of hypertensive patients. They reported that a continuous infusion of remifentanil in contrast to bolus administration maintained baseline blood pressures for a prolonged duration after intubation in hypertensive patients, regardless of antihypertensive drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the effect-site concentration (concentration of drug at the site of its biological activity) of remifentanil cannot be measured accurately. Maruta et al 13 calculated the effect-site concentrations of remifentanil based on a default formula from the electronic anesthesia record. We did not use a default program or a targetcontrolled infusion system; thus, it was not possible to estimate the effect-site concentration of remifentanil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of CPTP is not fully understood, but many patients experiencing CPTP have neuropathic pain rather than nociceptive pain (10). In chronic pain states, an inappropriate focus can be made of pain intensity.…”
Section: Introductionmentioning
confidence: 99%